Agile conversations transform your conservations, transform your culture - Squirrel, Douglas; Fredrick, Jeffrey (IT Revolution, 2020)
"Today, software organizations are transforming the way work gets done through practices like Agile, Lean, and DevOps. But as commonly implemented as these methods are, many transformations still fail, largely because the organization misses a critical step: culture and how people communicate. Agile Conversations brings an updated, practical, step-by-step guide to using the power of conversation to build effective, high-performing teams to achieve truly Agile results. To advance your organization's transformation, learn how to have productive conversations that overcome cognitive bias and fear. Consultants Douglas Squirrel and Jeffrey Fredrick show readers how to utilize the Five Conversations to help teams build trust, alleviate fear, answer the "whys," define commitments, and hold everyone accountable. These five conversations give teams everything they need to reach peak performance, and they are exactly what's missing from too many teams today. Stop focusing just on processes and practices that leave your organization stuck with culture-less rituals. Instead, unleash the unique human power of conversation"--
Includes bibliographical references. - Description based on online resource; title from digital title page (viewed on May 26, 2020)
Keywords: Communication in management; Teams in the workplace; Information technology -- Management; Communication en gestion; Équipes de travail; Technologie de l'information; Gestion; Information technology; Management